Answer:
[tex]K_A = 2K_B[/tex]
Explanation:
As we know that initial height of both the balls are same
also the mass of the two balls is given as
[tex]m_A = 2m_B[/tex]
so here we can say by mechanical energy conservation
initial total mechanical energy = final total mechanical energy
since both balls are initially at rest so initial total kinetic energy of the balls will be zero
now final total kinetic energy = initial total potential energy
now we say
[tex]K_A = m_A gh[/tex]
[tex]K_B = m_B gh[/tex]
so we have
[tex]\frac{K_A}{K_B} = \frac{m_A}{m_B}[/tex]
[tex]K_A = 2K_B[/tex]